Aumento da produção de fenazina-1-ácido carboxílico em E. coli: efeito da superexpressão dos genes tktA e ppsA - Altmann, Daniel Lossa (Universidade Federal de São Carlos, 2021)
Secondary metabolites known as phenazines are nitrogenated aromatic compounds produced particularly by the bacterium genera Pseudomonas and Streptomyces, with applications in fields like biological pest control and biosensors development, for instance. Their biosynthesis starts from chorismate, the final product of the shikimate pathway. Current studies to optimize their production rely on natural producers, but these organisms are generally pathogenic or show low productivities. In this study, the enzymes transketolase A (TktA) and phosphoenolpyruvate synthase (PpsA), which act in the formation of primary precursors of the shikimate pathway, were overexpressed in E. coli aiming to the heterologous synthesis of phenazine-1-carboxylic acid (PCA), the precursor of other phenazines. The tktA and ppsA genes were individually and combinatorically cloned on the pRSM4 plasmid, which was transformed into E. coli parental cells QH4 (ΔtyrA, ΔpheA), with the plasmid pETM7_phzABGFCDE (carrying the genes previously cloned from P. aeruginosa for PCA biosynthesis). All the strains were cultivated in baffled flasks, TB medium supplemented with 2% of glycerol, at 30 ºC, and 220 rpm, induced by IPTG 1mM. PCA and glycerol concentration were determined by HPLC, while the biomass was monitored by optical density readings of the culture broth. The highest PCA titers reached were 209 mg/L (ppsA individually overexpressed), 763 mg/L (tktA individually overexpressed), 523 mg/L (tktA and ppsA in monocistronic assembly), 628 mg/L (tktA and ppsA pseudo-operon assembly), and 275 mg/L (parental strain). Taken together, these results showed that the overexpression of TktA led to a great improvement of PCA production in E. coli, without affecting cellular growth. On the other hand, the overexpression of PpsA reduced the PCA titer and impaired cellular growth.
Improvement of phenazine-1-carboxylic acid production: effect of overexpression of tktA and ppsA genes
Keywords: Fenazinas; Engenharia metabólica; Compostos aromáticos; Via do chiquimato; Metabólitos secundários; Phenazines; Metabolic engineering; Shikimate pathway; Aromatic compounds; Secondary metabolites; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOQUIMICA DOS MICROORGANISMOS; CIENCIAS BIOLOGICAS::GENETICA::GENETICA MOLECULAR E DE MICROORGANISMOS; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA::MICROBIOLOGIA INDUSTRIAL E DE FERMENTACAO